Aplikasi Perkantoran Menggunakan Office untuk menghadapi Uji Kompetensi - buhori muslim; Eva Susilawati; Asep Syaputra; Sasmita (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
SMKN 1 Campaka carries out secondary level vocational education in Campaka, Cianjur Regency, regional secondary education institutions with all their problems are required to produce standard products (alumni) that are even able to be accepted and compete in the world of work with City Vocational Schools that are modern and good in providing advice, for the sake of Responding to challenges and beliefs in educating prospective alumni, SMKN 1 Campaka collaborates with various parties to improve quality alumni, a series of work skills training activities was held in collaboration with servants from UNPI Cianjur and Ghippams Academy, where a series of activities included training and competency tests, UNPI Cianjur provided resource persons for training and competency tests carried out by TUK Ghippams Academy from Cianjur, The practical learning method in this service has proven to be good, the training participants are able to absorb all the material presented and in the final questionnaire on understanding the training material 100% of the training participants can accept the material presented and consider it very good and useful to hold the training, able assist the implementation of the competency test carried out.